Comparative chloroplast genome analysis of Ficus (Moraceae): Insight into adaptive evolution and mutational hotspot regions - Zhang, Zheng-Ren; Yang, Xue; Li, Wei-Ying; Peng, Yan-Qiong; Gao, Jie (Frontiers in Plant Science, 2022)
As the largest genus in Moraceae, Ficus is widely distributed across tropical and subtropical regions and exhibits a high degree of adaptability to different environments. At present, however, the phylogenetic relationships of this genus are not well resolved, and chloroplast evolution in Ficus remains poorly understood. Here, we sequenced, assembled, and annotated the chloroplast genomes of 10 species of Ficus, downloaded and assembled 13 additional species based on next-generation sequencing data, and compared them to 46 previously published chloroplast genomes. We found a highly conserved genomic structure across the genus, with plastid genome sizes ranging from 159,929 bp (Ficus langkokensis) to 160,657 bp (Ficus religiosa). Most chloroplasts encoded 113 unique genes, including a set of 78 protein-coding genes, 30 transfer RNA (tRNA) genes, four ribosomal RNA (rRNA) genes, and one pseudogene (infA). The number of simple sequence repeats (SSRs) ranged from 67 (Ficus sagittata) to 89 (Ficus microdictya) and generally increased linearly with plastid size. Among the plastomes, comparative analysis revealed eight intergenic spacers that were hotspot regions for divergence. Additionally, the clpP, rbcL, and ccsA genes showed evidence of positive selection. Phylogenetic analysis indicated that none of the six traditionally recognized subgenera of Ficus were monophyletic. Divergence time analysis based on the complete chloroplast genome sequences showed that Ficus species diverged rapidly during the early to middle Miocene. This research provides basic resources for further evolutionary studies of Ficus.